Breast-Q® em reconstrução mamária com implante - Aguiar, Isabella de Carvalho [UNIFESP] (2016)
Background: Breast cancer is the second most common cancer worldwide and the most prevalent among women. Breast reconstruction plays an important role in the quality of life of patients with breast cancer. Purpose: To assess health-related quality of life and patient satisfaction after breast reconstruction with implants, using the BREAST-Q® in the late postoperative period. Methods: One hundred and fourteen women, aged 30 to 55 years, in the late postoperative period (range, 6-24 months) were selected to participate in this cross-sectional study, and were allocated to either the mastectomy group (n = 57) or reconstruction group (n = 57). The Brazilian version of the BREAST-Q®, a patient-reported outcome measure, was completed by all participants. Results: The mean age of patients was 46.6 and 44.3 years (P = 0.4080) in the mastectomy and reconstruction groups, respectively. All patients underwent chemotherapy and 6% and 11% of patients underwent radiotherapy (P = 0.2929) in the mastectomy and reconstruction groups, respectively. Patients in the reconstruction group reported higher satisfaction with breasts (P ? 0.0001) than those in the mastectomy group. However, no significant between-group differences were found in physical (P = 0.1616) and sexual (P = 0.5128) well-being, and satisfaction with the surgeon (P = 0.7147), medical team (P = 0.7488), and office staff (P = 0.8733). Conclusion: Breast reconstruction with implants increased patient satisfaction with breasts, but had no effect on patients? physical and sexual well-being, and satisfaction with the treatment received.